1988
DOI: 10.1038/bjc.1988.66
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MSA as a serum marker in breast cancer: A comparison with CEA

Abstract: Summary In a blind study, 518 serum samples were assayed for serum levels of mammary serum antigen (MSA) by an enzyme immunoassay (EIA) using the 3E1.2 monoclonal antibody. Using 300 IU as the arbitrary cut off to distinguish normal from abnormal individuals, 75% of patients with primary Stage I carcinoma of the breast (n = 12), 89% (Stacker et al., 1987).Other workers have produced monoclonal antibodies which define high molecular weight glycoproteins in the serum of patients with breast cancer (Hayes et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

1988
1988
1995
1995

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
0
9
1
Order By: Relevance
“…Serum CEA has been examined in combination with a number of monoclonal antibodies raised to tumour associated antigens -e.g. MAM-6 antigen, 11 5D8 (Hilkens et al, 1987), antigen (Hayes et al, 1986;Fujino et al, 1986;Pons-Anicet et al, 1987;Kallioniemi et al, 1988;Tondini et al, 1988;Delarue et al, 1988) and mammary serum antigen (MSA) (Stacker et al, 1988). Other newer monoclonal antibodies have been reported such as MCA (Stahli et al, 1989), CA 549 (Bray et al, 1989) and CA M26 and CA M29 (van Ramp et al, 1989).…”
mentioning
confidence: 99%
“…Serum CEA has been examined in combination with a number of monoclonal antibodies raised to tumour associated antigens -e.g. MAM-6 antigen, 11 5D8 (Hilkens et al, 1987), antigen (Hayes et al, 1986;Fujino et al, 1986;Pons-Anicet et al, 1987;Kallioniemi et al, 1988;Tondini et al, 1988;Delarue et al, 1988) and mammary serum antigen (MSA) (Stacker et al, 1988). Other newer monoclonal antibodies have been reported such as MCA (Stahli et al, 1989), CA 549 (Bray et al, 1989) and CA M26 and CA M29 (van Ramp et al, 1989).…”
mentioning
confidence: 99%
“…an IgM (8) and HMFG-1, an igGl (9). Another monoclonal antibody (MoAb) used was 3EI 2 (IgM) thai was developed against primary breast carcinoma (10); it detected a high molecular weight glycoprotein in breast cancer tissue and sera but had a weak or no reaction with components ofthe human milk (11). MoAbs were purified from ascitic fluid: IgG antibodies by protein A-Sepharose (Pharmacia Inc.. Piscataway.…”
Section: Monoclonal Antibodies and Iodinationmentioning
confidence: 99%
“…Human milk fat globule membrane (HMFGM) was isolated from fresh human milk as previously described (21). The aetivity ofthe antibody RCC-I was assessed by its binding to T47D membrane in an enzyme linked immunosorhent assay (ELISA) (11). T47D membrane was coated in carbonate buffer.…”
Section: Serological Analysis Of Serum Samples and Human Milkmentioning
confidence: 99%
“…In addition, changes in MSA level have been shown to correlate with the clinical course and precede disease progression (Tjandra et al, 1988). In a preliminary study, MSA measurement was also found to be more sensitive than the currently available tumour markers (CA15-3 and CEA) for the detection of breast cancer Stacker et al, 1988 (Bearhs & Myers, 1983). The MSA levels were determined and a level of 300 IU was considered to be the upper limit of normal (mean +2 s.d.)…”
mentioning
confidence: 99%